Are the old International Board for Plant Genetic Resources (IBPGR) base collections available through the Plant Treaty’s multilateral system of access and benefit sharing? A review - Thormann, I.; Engels, I.; Halewood, Michael (Springer, 2019)
In 1975, the International Board for Plant Genetic Resources created the first internationally linked system of genebanks, known as the Registry of Base Collections (RBC), to conserve plant germplasm and make it available globally for agricultural research and development. Over time, international efforts shifted away from enhancing and building the RBC toward other means to promote the conservation and sustainable use of plant genetic resources. Perhaps the most important development in this regard was the negotiation of the International Treaty on Plant Genetic Resources for Food and Agriculture (Plant Treaty or ITPGRFA) and the development of its multilateral system for access and benefit sharing (multilateral system). Our study aimed to ascertain whether the RBC materials are still being conserved/curated in the original recipient organizations. We also sought to assess whether those materials have been included in, and are available through, the ITPGRFA’s multilateral system. This outcome would be significant since, in many ways, the multilateral system reflects the spirit, commitment, and objectives of the RBC, with important additional components (e.g. obligations to share monetary benefits derived from the uses of plant genetic resources for food and agriculture). We identify four levels of probability that RBC materials are included in, and available through, the multilateral system. Ultimately, we find that there is a high level of probability that approximately 80% of the RBC materials are currently available through the multilateral system. We further identify a number of possible interventions that could be made to ensure that all RBC materials are conserved and made available through the multilateral system (or on similar terms and conditions of facilitated access and benefit sharing).